MicroRNAs are involved in the hypothalamic leptin sensitivity. Issue 10 (2nd November 2018) - Derghal, Adel; Djelloul, Mehdi; Azzarelli, Myriam; Degonon, Sébastien; Tourniaire, Franck; Landrier, Jean-François; Mounien, Lourdes
ABSTRACT: The central nervous system monitors modifications in metabolic parameters or hormone levels (leptin) and elicits adaptive responses such as food intake and glucose homeostasis regulation. Particularly, within the hypothalamus, pro-opiomelanocortin (POMC) neurons are crucial regulators of energy balance. Consistent with a pivotal role of the melanocortin system in the control of energy homeostasis, disruption of the Pomc gene causes hyperphagia and obesity. Pomc gene expression is tightly controlled by different mechanisms. Interestingly, recent studies pointed to a key role for micro ribonucleic acid (miRNAs) in the regulation of gene expression. However, the role of miRNAs in the leptin sensitivity in hypothalamic melanocortin system has never been assessed. We developed a transgenic mouse model (PDKO) with a partial deletion of the miRNA processing enzyme DICER specifically in POMC neurons. PDKO mice exhibited a normal body weight but a decrease of food intake. Interestingly, PDKO mice had decreased metabolic rate by reduction of VO2 consumption and CO2 production which could explain that PDKO mice have normal weight while eating less. Interestingly, we observed an increase of leptin sensitivity in the POMC neurons of PDKO mice which could explain the decrease of food intake in this model. We also observed an increase in the expression of genes involved in the function of brown adipose tissue that is in polysynaptic contact with the POMC neurons. In summary, these results support the hypothesis that Dicer-derived miRNAs may be involved in the effect of leptin on POMC neurons activity.